2003
DOI: 10.2166/wst.2003.0386
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of octylphenol polyethoxylates by denitrification

Abstract: The biodegradation route of the octylphenol ethoxylates (OPEOs) by denitrification in an upflow anoxic sludge blanket (UASB) reactor was studied. An anaerobic sludge adapted to denitrifying conditions with acetate was adapted with increasing amounts of OPEOs and diminishing amounts of acetate until only 300 mg x L(-1) of OPEOs were fed. Only 70% of stoichiometric NO3- was fed so partial removal was expected. The total OPEOs fed was transformed with 70% COD removal. HPLC and GC-MS analyses showed that octylphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
(12 reference statements)
0
8
0
Order By: Relevance
“…Therefore, as the shortening of the ethoxy chain progresses, the breakdown products are more likely adsorbed to the organic phases of the sludge and suspended solids (John et al, 2000). In effect, the rapid disappearance of newly formed OP from the aqueous phase of an upflow anoxic sludge blanket reactor continuously fed with octylphenol polyethoxylates was rationalized in terms of sorption to the sludge components (Jimenez-Gonzalez et al, 2003). However, sorption characteristics may vary with the substrate and with the type of organic matter (Moore and Matos, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as the shortening of the ethoxy chain progresses, the breakdown products are more likely adsorbed to the organic phases of the sludge and suspended solids (John et al, 2000). In effect, the rapid disappearance of newly formed OP from the aqueous phase of an upflow anoxic sludge blanket reactor continuously fed with octylphenol polyethoxylates was rationalized in terms of sorption to the sludge components (Jimenez-Gonzalez et al, 2003). However, sorption characteristics may vary with the substrate and with the type of organic matter (Moore and Matos, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The extent of anaerobic degradation appears to be slower (Salanitro and Diaz, 1995;Ferguson and Brownawell, 2003), but proceeds one step further to form NP as the ultimate degradation product (Ejlertsson et al, 1999). Despite the environmental significance of nitrate as electron acceptor, there are only few (and conflicting) reports about APEOs degradation under nitrate-reducing conditions (Jimenez-Gonzalez et al, 2003;Chang et al, 2004;Mohan et al, 2006). Further understanding of the mechanisms of anaerobic transformation of NPEO in the environment has been hampered by the lack of clear evidence of the nitrate-dependent, anaerobic degradation of NPEO.…”
Section: Introductionmentioning
confidence: 99%
“…The same results were described for anaerobic biodegradation under denitrifying, sulfate-reducing, and iron(III)-reducing conditions [ 69 , 70 , 71 ]. The metabolite alkyl phenol is poorly degradable both under aerobic and anaerobic conditions and affects the aquatic environment due to its proven estrogenic activity [ 72 ].…”
Section: Anaerobic Biodegradability Of Different Types Of Detergenmentioning
confidence: 99%
“…(II) ω -Carboxylation of the ethoxylated chain, yielding different polyethoxylated derivatives, being the most abundant the diethoxylated species (NPEO 2 C); simultaneously, it is possible that the oxidation of the nonyl chain generates dicarboxylic compounds (CNPEO 1 C), without production of nonylphenol [12]. (III) Simultaneous shortening of the ethoxylated and alkylic chains to produce propyl and heptyl diethoxylated compounds [2] and (IV) oxidation of the polyethoxylated chain, without any shortening, to yield the corresponding carboxylic acids [27, 28]. Besides, it has been reported that the initial step in the NPEO x degradation occurs on the ethoxylated moiety of the molecule, followed by further attack on the aromatic nonylphenol ring [29].…”
Section: Introductionmentioning
confidence: 99%